Evaluating the Potential Returns to Investing in Green Urban Development in Durban - Turpie, Jane (World Bank, Washington, DC, 2017)
Urbanisation is taking place at an unprecedented rate throughout the world, often outpacing plans and the capacity of city managers. As a result, natural open space areas in cities are being degraded and diminished, and problems such as flooding, air and water pollution are getting worse. The environmental problems associated with increased hardened surfaces and the loss of natural areas and ecosystem services are particularly acute in developing country cities, where a lack of regulation and resources has led to poor planning, the expansion of informal settlements in high risk, marginal areas, and the inability to adequately manage the quantity and quality of surface water flows.Durban, located within the eThekwini Municipality on the east coast of South Africa, is rich in biodiversity, but faces a number of environmental and developmental challenges. Green urban development is an approach that aims to minimize the impacts of urbanization on the environment, and tackles the core problems of pollution and waste, the consumption of natural resources, the loss of urban open space and the degradation and loss of biodiversity, as well as mitigation of the urban contribution to climate change. The aim of this study was to explore, using a case study and scenario-based approach, the potential costs and benefits of undertaking a green urban development approach to address some of the main environmental issues described above, and to explore the potential tradeoffs between different types of interventions, with an emphasis on assessing the desirable balance between engineered interventions and the conservation of natural open space areas. The study focuses on three elements of green urban development, all of which impact on ecosystems and biodiversity: sewage and solid waste management, active storm water management and the conservation of natural systems and riparian corridors.